PENERAPAN METODE AGILE DALAM PENGEMBANGAN SISTEM PEMESANAN ONLINE BERBASIS WEB (STUDI KASUS: MERCY’S COFFEE) - Nugraha, Titto (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The advancement of information technology demands efficient and adaptive systems in the food and beverage sector. Mercy’s Coffee, which still uses a manual ordering process, faces challenges such as long queues, slow service, and frequent order errors. This study aims to design and develop a web-based online ordering system using the Agile methodology with the Scrum framework, enabling iterative development and continuous improvements based on user feedback. The research process includes requirement analysis, system design with Unified Modeling Language (UML), frontend development using Tailwind CSS and React.js, and backend implementation with Express.js and MySQL. System testing using Blackbox Testing confirmed that all main features, including menu ordering, order management, digital payment, and real-time order status tracking, operate effectively. The system enhances operational efficiency, accelerates transactions, reduces input errors, and provides a more responsive and structured user experience. Applying Agile with Scrum in this development serves as a valuable reference for developers and business owners in creating digital systems that emphasize flexibility, collaboration, and customer satisfaction.